1980
DOI: 10.1038/bjc.1980.301
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect in vivo of selected chemotherapeutic agents on synchronized murine fibrosarcoma cells

Abstract: Summary.-The cytotoxic effects in vivo of single doses of either adriamycin (ADM), 1-p -D-arabinofuranosylcytosine (Ara-C), bleomycin (BLM), cis-diamminedichloroplatinum (II) (cis-DDP), or cyclophosphamide (CY) on murine fibrosarcoma (FSa) cell populations were determined. Tumour cells were separated and synchronized by centrifugal elutriation. Viable tumour cells from selected elutriator fractions were then injected i.v. into whole-body-irradiated mice. Twenty minutes later selected doses of ADM, Ara-C, BLM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Other workers using c-DDP on cells both in vitro (Meyn et al 1980, Roberts andFraval 1980) and in vivo (Grdina et al 1980), have demonstrated greatest sensitivity to the drug in G1 and least sensitivity in S, i.e. similar to X-rays.…”
Section: Radiosensitization By Cisplatinmentioning
confidence: 97%
“…Other workers using c-DDP on cells both in vitro (Meyn et al 1980, Roberts andFraval 1980) and in vivo (Grdina et al 1980), have demonstrated greatest sensitivity to the drug in G1 and least sensitivity in S, i.e. similar to X-rays.…”
Section: Radiosensitization By Cisplatinmentioning
confidence: 97%
“…In an excellent review in which the varying results of BLM in CHO, Hela, and human lymphoma cells by a number of authors are discussed, Twentyman [20] concludes that it is difficult to arrive at any generally-useful conclusions regarding the cell cycle phase specificity of BLM. There appears to be general agreement on the mitotic sensitivity being the greatest for BLM, but little other agreement for the other cell phases [1,20,21]. A more useful generalization for cell cycle age response is found for ADR.…”
mentioning
confidence: 90%
“…Recently, a simple in vivo procedure has been developed and described for characterizing the phase-specific therapeutic effectiveness of selected cytotoxic agents [6,11,12]. This procedure entails the i.v.…”
Section: Introductionmentioning
confidence: 99%